Pengaruh Gaya Kepemimpinan, Motivasi dan Disiplin Kerja Terhadap Kinerja Pegawai PT. Hokinda Citralestari - Juniarta Rajagukguk; Kristina Peritua Aruan; Grace Theresia Silaban; Rafida Khairani (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
This study aims to determine the influence of leadership style on employee performance at PT Hokinda Citralestari, determine the effect of motivation on employee performance at PT Hokinda Citralestari, determine the effect of work discipline on employee performance at PT Hokinda Citralestari and to know the influence of leadership style, motivation and work discipline simultaneously on employee performance at PT Hokinda Citralestari. This research is descriptive quantitative with the instrument the questionnaire with the number of the population of all employees of PT Hokinda Citralestari as many as 400 people next calculated the Slovin formula so obtained a sample of 80 people. The results of the research obtained Value of the coefficient of t leadership style is 2,239 and the value of ttable of 1,990, where tcount > ttable (2,239 > 1,990) the value of sig < 0,05 (0,028 < 0.05), the coefficient value of tcount motivation is 2,923 and the value of ttable of 1,990, where tcount > ttable (2,923 > 1,990) the value of sig < 0,05 (0,005 < 0,05), the Value of the coefficient t work discipline is 2,148 and the value of ttable of 1,990 where tcount > ttable (2,148 > 1,990) the value of sig < 0,05 (0,035< 0,05). Furthermore, the value of Fcount variables of leadership style, motivation and work discipline is 30,239 with a sig value of 0.000 and the value of Ftable of 2,720 where Fcount > Ftable (30,239 > 2,720) the value of sig < 0,05 (0,000 < 0,05). The value of adjusted R-square that is 0,526 or adjusted R2 x 100% of 52,60%, meaning that the independent variables of the study provide significant contribution in explaining about the performance of employees at 52,60% while the rest 47,40% influenced by other factors.